Atomic-level passivation mechanism of ammonium salts enabling highly efficient perovskite solar cells - Essa A. Alharbi (Nature Portfolio, 2019)
Various approaches have been developed to push higher the efficiency of halide perovskite solar cells. Here Alharbi et al. show that ammonium salts treatment can reduce the defect density at the perovskite surface and understand the passivation mechanism with 2D-solid state NMR.